[​4+2] versus [​2+2] Homodimerization in P(V) Derivatives of 2, 4-Disubstituted Phospholes. (1st April 2019) - Bousrez, Guillaume; Nicolas, Emmanuel; Martinez, Agathe; Chevreux, Sylviane; Jaroschik, Florian
Abstract : Phosphole P(V) derivatives are interesting building blocks for various applications from ligand synthesis to material sciences. We herein describe the preparation and characterisation of new 2, 4-disubstituted oxo-, thiooxo-, and selenooxophospholes. The nature of the substituents on the phosphole ring determines the reactivity of these compounds towards homodimerization reactions. Aryl and trimethylsilyl substituted oxophospholes undergo selective[ 4+2] dimerization, whereas, for thiooxo- and selenooxophospholes, light-induced, selective[ 2+2] head-to-head dimerization occurs in the case of aryl substituents. DFT calculations provide some insights on these differences in reactivity.